2012
DOI: 10.1097/dcr.0b013e31823461ef
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Cap-Assisted Colonoscopy Versus Standard Adult Colonoscopy

Abstract: Cap-assisted colonoscopy is associated with improved detection of colorectal neoplasia and higher cecal intubation rates than standard adult colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 36 publications
3
56
1
Order By: Relevance
“…Despite this evidence, studies of cap-assisted colonoscopy still report conflicting clinical results. The use of caps is associated with a statistically significant reduction in time to caecal intubation, but not a better caecal intubation or polyp detection rate, as confirmed in other two meta-analyses [2,3]. Moreover, the average reduction in time to caecal intubation of only 48 s shown in the present meta-analysis does not make it possible to put more patients on the endoscopy list.…”
supporting
confidence: 52%
“…Despite this evidence, studies of cap-assisted colonoscopy still report conflicting clinical results. The use of caps is associated with a statistically significant reduction in time to caecal intubation, but not a better caecal intubation or polyp detection rate, as confirmed in other two meta-analyses [2,3]. Moreover, the average reduction in time to caecal intubation of only 48 s shown in the present meta-analysis does not make it possible to put more patients on the endoscopy list.…”
supporting
confidence: 52%
“…We assume that the HD+i-SCAN colonoscope will not help to inspect the blind mucosa and therefore will not have any impact on the detection of missed lesions on the reverse side of the mucosal folds. Other recently developed ancillary techniques that may assist in detecting hidden lesions in the blind mucosal surface, such as cap-assisted, Endocuff, EndoRing, and balloon colonoscopies, work on the principle of flattening the haustral folds during withdrawal and, therefore, expanding the surface area of the colonic mucosa being visualized; the Third Eye Retroscope retrograde-viewing auxiliary device, or wider angle colonoscopes can be useful adjuncts (32)(33)(34)(35)(36). In conclusion, our study found that the use of a HD+i-SCAN colonoscope yielded an increase in flat ADR compared to a SRWL colonoscope in average-risk CRC screening colonoscopies.…”
Section: Discussionmentioning
confidence: 99%
“…al. 9 reported a miss-rate of 12.2% in the cap-assisted colonoscopy group vs. 28.6% miss rate in the standard colonoscopy group, implying a positive effect of cap employment on polyp detection rate. In contrast, another study performed by Tee et.…”
Section: Introductionmentioning
confidence: 99%